Gender Perspectives on Academic Leadership in African Universities - Diab, Roseanne; Kalele, Phyllis; Bulani, Muthise; Boateng, Fred K.; Mukeshimana, Madeleine (International Journal of African Higher Education, 2024)
Women are under-represented in higher education leadership across the globe, with the gender gap in Africa being even more pronounced. This article reports gender-disaggregated statistics for senior academic leadership at 16 African research-intensive universities. The gender gap at the level of Vice-Chancellor (VC), the executive head of the university, is striking and is replicated at each leadership level. Women represented only 13% of VCs, half the universities had fewer than 50% women in their executive teams and half had fewer than 30% female Deans. The article also presents the results of an online survey instrument that was administered to faculty members at Deans’ level and above at six of the institutions spread across South Africa, Ghana, and Rwanda to gain insights into women’s academic leadership. Women ranked competence and experience as the most important factors in their leadership accession, indicative of belief in their own abilities and self-worth. They expressed a need for mentoring, measures to address discrimination and greater visibility. A wide gap was evident in men’s and women’s understanding of obstacles to more women occupying leadership positions. Men placed responsibility for the gender gap on women, stating that few are suitably qualified, and that women do not aspire to senior leadership positions. For their part, women pointed to systemic institutional failures as responsible for their under-representation.